СТРУКТУРНЫЕ КОМПОНЕНТЫ МОДЕЛИ СОВРЕМЕННОГО ПСИХОЛОГА - Нурымбетова, Э.Ж. (SCIENCE and SOCIETY, 2023)
The article offers a model toolkit of the modern psychologist, which is based on the previously highlighted, based on the results of theoretical analysis, generalized professional and important qualities of a psychologist, combined into the appropriate structural components.